Short-term ageing effects on asphalt binders - Tiong, Hwa Nguong (2008)
Asphalts undergo two substantially different ageing processes in their service life. They are subjected to high temperatures and a high degree of air exposure during their relatively short production time (short term ageing) and then to the environment at a relatively lower temperature and air void content for a long duration (long-term ageing). A variety of methods have been proposed and investigated to simulate the aging effects on asphalt during mixing as well as field service. Only short-term ageing was pursuit in this study, where the thin film oven test and rolling thin film oven test will be utilized to simulate the ageing. There is no direct measure for asphalt binder ageing. Rather, ageing effects are accounted for by subjecting asphalt samples to simulated ageing and conducting other standard physical tests (such as viscosity, penetration, and softening point) afterwards. The main purpose of this study was to compare the ageing effects from both ageing methods for three types of asphalt binders. From the t-test analysis, the two ageing methods result in almost similar rheological properties (p > 0.05).